How to reduce the IT gender gap in occupational preferences? - Bajka, Scherwin M. [Verfasser]; Emmenegger, Patrick [Verfasser] (My University, 2026)
“As the demand for information technology (IT) skills increases, occupational gender segregation has gained new relevance. A large body of research suggests that women are less attracted to technology-reliant occupations (things) than men are. Instead, women prefer occupations that emphasize social interactions (people). This study adds to the literature on the people versus things trade-off in occupational preferences by examining the underlying role of individuals’ perceptions of IT. We argue that perceptions of IT are socially constructed, which allows for different presentations of occupational tasks and skill requirements. Surveying the occupational preferences of 2,500 eighth-grade students in Switzerland, we find that while girls prefer occupations with frequent social interactions but low reliance on IT, boys do not perceive a trade-off between working with people and working with things. Additionally, we show that boys and girls associate different features with IT and that these associations matter for their occupational preferences. Specifically, associating IT with frequent social interactions makes IT-reliant occupations more attractive for both genders, although girls are less likely than boys to associate IT with social interactions. Finally, we demonstrate that IT-reliant occupations become more attractive to girls when the presentation emphasizes the interactive and social aspects of work.“ (authors‘ abstract; BIBB-Doku)

"IT-Berufe sprechen hauptsächlich Jungen und Männer an. Warum ist das so und lässt sich dies ändern? Eine in der European Sociological Review veröffentlichte Studie von Scherwin Bajka und Patrick Emmenegger (HSG) zeigt: Um mehr Mädchen für Informatikberufe zu gewinnen, sollten bestehende Berufsbilder kritisch hinterfragt und realistischer vermittelt werden. Denn Mädchen nehmen, so die Studie, IT-Berufe häufig als rein technisch wahr und kaum als sozial interaktiv. Dabei sei der Berufsalltag stark von Austausch, Teamarbeit und Kundenkontakt geprägt. Berufsorientierung sollte deshalb die sozialen Aspekte technischer Berufe stärker hervorheben und frühzeitig mit stereotypen Vorstellungen aufräumen." (BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; S 6.3 Technische Berufe; G 2.4.5 Gender Mainstreaming; 370; Berufsorientierung; Technischer Beruf; IT-Beruf; Wahrnehmung; Stereotyp; Geschlechterrolle; Berufswunsch